Application of Ensite™ LiveView function for identification of scar‐related ventricular tachycardia isthmus. (25th March 2022) - Kao, Pei‐Heng; Chung, Fa‐Po; Lin, Yenn‐Jiang; Chang, Shih‐Lin; Lo, Li‐Wei; Hu, Yu‐Feng; Tuan, Ta‐Chuan; Chao, Tze‐Fan; Liao, Jo‐Nan; Lin, Chin‐Yu; Chang, Ting‐Yung; Kuo, Ling; et al.
Abstract: Introduction: Dynamic display of real‐time wavefront activation pattern may facilitate the recognition of reentrant circuits, particularly the diastolic path of ventricular tachycardia (VT). Objective: We aimed to evaluate the feasibility of LiveView Dynamic Display for mapping the critical isthmus of scar‐related reentrant VT. Methods: Patients with mappable scar‐related reentrant VT were selected. The characteristics of the underlying substrates and VT circuits were assessed using HD grid multielectrode catheter. The VT isthmuses were identified based on the activation map, entrainment, and ablation results. The accuracy of the LiveView findings in detecting potential VT isthmus was assessed. Results: We studied 18 scar‐related reentrant VTs in 10 patients (median age: 59.5 years, 100% male) including 6 and 4 patients with ischemic and nonischemic cardiomyopathy, respectively. The median VT cycle length was 426 ms (interquartile range: 386–466 ms). Among 590 regional mapping displays, 92.0% of the VT isthmus sites were identified by LiveView Dynamic Display. The accuracy of LiveView for isthmus identification was 84%, with positive and negative predictive values of 54.8% and 97.8%, respectively. The area with abnormal electrograms was negatively correlated with the accuracy of LiveView Dynamic Display ( r  = −.506, p  = .027). The median time interval to identify a VT isthmus using LiveView was significantly shorter than that using conventional activation maps (50.5 [29.8–120] vs. 219 [157.5–400.8] s, p  = .015). Conclusion: This study demonstrated the feasibility of LiveView Dynamic Display in identifying the critical isthmus of scar‐related VT with modest accuracy.